2017
DOI: 10.1140/epjc/s10052-017-5010-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical attributes of anisotropic compact stars in f(R, G) gravity

Abstract: Modified gravity is one of the potential candidates to explain the accelerated expansion of the universe. Current study highlights the materialization of anisotropic compact stars in the context of f (R, G) theory of gravity. In particular, to gain insight in the physical behavior of three stars namely, Her X 1, SAX J 1808-3658 and 4U 1820-30, energy density, and radial and tangential pressures are calculated. The f (R, G) gravity model is split into a Starobinsky like f (R) model and a power law f (G) model. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Other models considered in the literature are: f (R, R 2 GB ) gravity, which has been studied with anisotropic fluids but isotropic EOS [341,342,343], (anisotropic) stars in non-minimal gravity-electromagnetic coupling models of type f (R)F µν F µν [344] and even with more involved couplings [345], other models with non-minimally coupled scalar fields with several realistic EOS [348], corrections in the Lagrangian density in scalars of the energy-momentum tensor such as T µν T µν [349] with polytropic and strange quark matter (all these yielding slight to moderate increases on the maximum allowed mass depending on the EOS chosen); and scalar-tensor-vector theories [350], where FPS, SLy and BSK21 EOS yield small to moderate increases of M ⋆ for astrophysically viable model parameters.…”
Section: Further Considerationsmentioning
confidence: 99%
“…Other models considered in the literature are: f (R, R 2 GB ) gravity, which has been studied with anisotropic fluids but isotropic EOS [341,342,343], (anisotropic) stars in non-minimal gravity-electromagnetic coupling models of type f (R)F µν F µν [344] and even with more involved couplings [345], other models with non-minimally coupled scalar fields with several realistic EOS [348], corrections in the Lagrangian density in scalars of the energy-momentum tensor such as T µν T µν [349] with polytropic and strange quark matter (all these yielding slight to moderate increases on the maximum allowed mass depending on the EOS chosen); and scalar-tensor-vector theories [350], where FPS, SLy and BSK21 EOS yield small to moderate increases of M ⋆ for astrophysically viable model parameters.…”
Section: Further Considerationsmentioning
confidence: 99%
“…Moreover, the existence of this symmetry leads to a specific form of the unknown functions that appear in the Lagrangian. The method is used to obtain cosmological models in several alternative theory of gravity, for example, scalar tensor theory [83][84][85][86][87][88][89][90][91][92][93][94], f (R) theory [25,26,[95][96][97][98][99][100][101][102], f (T ) theory [103][104][105][106][107][108][109][110], the theories of gravity with a fermionic field [13][14][15][16] and others [111][112][113][114][115][116][117][118][119]. With the help of Noether symmetry, some cosmological analytical solutions for the scalar tensor TG were obtained in Ref [65,120].…”
Section: Introductionmentioning
confidence: 99%
“…Laurentis and Lopez-Revelles [34] discuss the detail investigation of the weak field limit of f (R, G) gravity taking into consideration an analytic functions of the Ricci scalar R and the Gauss-Bonnet invariant G, specifically by developing in metric formalism, the Newtonian, Post-Newtonian and Parametrized Post-Newtonian limits starting from general f (R, G) Lagrangian and observed the Newtonian limit of f (R, G) gravity. Shamir and Zia [35] highlighted the materialization of anisotropic compact stars namely Her X1, SAX J 1808-3658, and 4U 1820-30 in the context of f (R, G) theory of gravity and have shown that all three stars behave as usual as for positive values of the f (G) model parameter n. In this work, we obtain the solution of field equations and the behavior of the universe using some kinematical and physical quantities for the f (R, G) gravity model i.e.…”
Section: Ijgmmp-d-19-00459mentioning
confidence: 99%